Synoptic weather systems over Antarctic sea ice: understanding the link between extratropical cyclones and extreme variability in Antarctic sea-ice concentration - Hepworth, Ehlke (Department of Oceanography, 2026)
Extratropical cyclones and atmospheric rivers are key drivers in transporting extreme heat and moisture to the poles. Previous studies have shown that extratropical cyclones can promote change in sea-ice concentration at a synoptic scale, however, the extreme variability in synoptic-scale sea-ice concentration and the extent to which it is engendered by cyclones has not yet been studied. This thesis seeks to quantify extreme variability of Antarctic sea-ice concentration, and assess the role that cyclones and other synoptic features play over the extended Austral winter period (May - September). This is achieved through the use of reanalyses data (based on the European Centre for Medium-Range Weather Forecasts; ERA-Interim and ERA5) and output from a climate model tuned for representing Southern Hemisphere processes, whose atmospheric component is the Conformal Cubic Atmospheric Model (CCAM). To accomplish this, this study is formulated about three main research aims. The first aim is to test whether circulation patterns associated with cyclones or atmospheric rivers may routinely lead to the presence of unusually warm, moist air masses over ice-covered regions. This thesis points to a strong association between atmospheric rivers and extreme moisture anomalies found over the Antarctic sea-ice environment, while extreme temperature anomalies over Antarctic sea ice are relatively linked with intense cyclones. More specifically, approximately 27% of intense Southern Ocean cyclones and 20% of ARs occur in the vicinity of extreme temperature anomalies, while 12% of intense cyclones and 46% of ARs occur in the vicinity of extreme moisture anomalies. These results, showing that extratropical cyclones play a role in weather circulations over the sea-ice environment, lead to this study's second research aim: to identify extreme variability in Antarctic sea-ice concentration and investigate the extent to which it may be caused by extratropical cyclones. Atmospheric reanalysis and a cyclone-tracking algorithm were used to characterize sea-ice variability and cyclone activity in different Southern Ocean sectors: the King Haakon VII, East Antarctic, Ross/Amundsen, Bellingshausen, and Weddell sectors. The proportion of extreme sea-ice variability engendered by cyclones of different intensities was quantified, and reveals a significant link between variability in winter sea-ice concentration and: (i) all cyclones in the Ross/Amundsen sector; (ii) all but the weakest cyclones in the King Haakon VII, East Antarctic, and Bellingshausen sectors; and (iii) all but the most intense cyclones in the Weddell sector. More generally, roughly 30 - 40% of the extreme sea-ice variability is caused by extratropical cyclones within all regions apart from the Weddell sector, where extreme sea-ice variability is more closely connected to weaker cyclones. Finally, the third research aim is to explore the relationship between cyclones and synoptic-scale variability in sea-ice concentration in a climate model, CCAM, where simulated sea-ice variability is dynamically driven by the model atmosphere (unlike the second research aim which used the ERA5 reanalysis product). Whilst the use of ERA5 revealed an emphasis on intense cyclones engendering extreme variability, the results derived from the analysis using CCAM showed that extreme variability in sea-ice concentration only depended on cyclone intensity in the East Antarctic sector. In the other sectors, on average, cyclones of all intensities (apart from the 10% weakest ones) had a significant link to extreme variability in sea-ice concentration at a synoptic scale. Moreover, using CCAM, the total extreme variability in sea-ice concentration linked to cyclones increased to roughly 40 - 60%. In conclusion, the Antarctic atmosphere-ice interplay over the extended Austral winter period is complex, but the results presented in this thesis shed new light on the relationship between synoptic features over the sea-ice environment, and the role cyclones play in engendering extreme variability in sea-ice concentration. As the atmosphere continues to change with global warming, the results presented in this thesis serve as a foundation for further investigations into how the Antarctic sea-ice environment may also change over time